2019
DOI: 10.3897/zookeys.838.32022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for cryptic species in the common slug eating snake Duberria lutrix lutrix (Squamata, Lamprophiidae) from South Africa

Abstract: We examined the impact of climatic fluctuations on the phylogeographic structure of the common slug eating snake (Duberrialutrixlutrix) throughout its distribution in South Africa. The evolutionary history within the taxon was examined using partial DNA sequence data for two mitochondrial genes (ND4 + cytb) in combination with a nuclear locus (SPTBN1). Phylogenetic relationships were investigated for both the combined mtDNA and total evidence DNA sequence data. In addition, population and demographic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…A study on the semiterrestrial swamp forest crab, Potamonautes lividus, revealed Pleistocene divergence of two reciprocally monophyletic mtDNA clades that coincide with specimens from the two provinces in the present study (Daniels et al, 2020). Other phylogenetic and phylogeographic studies on snakes (Kulenkampff et al, 2019), velvet worms (Daniels et al, 2016) and chameleons (Tolley et al, 2008) in the MPA have also revealed similar latitudinal structuring.…”
Section: Other Studies In the Mpa Biodiversity Hotspotsupporting
confidence: 80%
“…A study on the semiterrestrial swamp forest crab, Potamonautes lividus, revealed Pleistocene divergence of two reciprocally monophyletic mtDNA clades that coincide with specimens from the two provinces in the present study (Daniels et al, 2020). Other phylogenetic and phylogeographic studies on snakes (Kulenkampff et al, 2019), velvet worms (Daniels et al, 2016) and chameleons (Tolley et al, 2008) in the MPA have also revealed similar latitudinal structuring.…”
Section: Other Studies In the Mpa Biodiversity Hotspotsupporting
confidence: 80%
“…The two mtDNA loci selected were cytochrome b ( cyt b ) and nicotinamide adenine dinucleotide dehydrogenase subunit 4 ( ND4 ). The latter two mtDNA loci are widely used in reptile phylogeographic studies (Vidal et al, 2008; Makhubo, Tolley, & Bates, 2015; Medina et al, 2016; Blair & Bryson, 2017; Díaz et al, 2017; Portillo et al, 2018; Kullenkampff et al, 2019). The primer pairs ND4 (5′‐ACC TAT GAC TAC CAA AAG CTC ATG TAG‐3′) (Arévalo, Davis, & Sites, 1994) and H12763V (5′‐TTC TAT CAC TTG GAT TTG CAC CA‐3′) (Barlow et al, 2013) were used to amplify ± 890 base pairs (bp) of the ND4 locus, while ± 650 bp were amplified for the cyt b region using the primer pairs WWF (5′‐AAA YCA YCG TTG TWA TTC AAC TAC‐3′) and R2 (5′‐GGG TGR AAK GGR ATT TTA TC‐3′) (Whiting, Bauer, & Sites, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Climatic oscillations are thought to have driven cladogenesis and phylogeographic structuring in several southern African reptile taxa (Barlow et al, 2013; da Silva & Tolley, 2017; Diedericks & Daniels, 2013; Engelbrecht, vanNiekerk, Heideman, & Daniels, 2013; Stanley & Bates, 2014). In addition, divergence‐time estimates have demonstrated that cladogenesis among southern African reptile taxa closely mirror periods characterized by climatic ameliorations throughout the Mio/Plio/Pleistocene (Kullenkampff, Van Zyl, Klaus, & Daniels, 2019; Medina et al, 2016; Tolley, Chase, & Forest, 2008; Weinell & Bauer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, this remains a challenge due to the existence of cryptic species and species complexes. This may be a result of the long and complex evolution of reptiles, which first appeared on Earth more than 250 million years ago 1 , 5 7 . Among the Gekkonids (geckos), which is a group of lizards (Sauria), the most diverse group of reptiles in the world, the taxonomy of numerous species, including Hemidactylus 8 10 , Hemiphyllodactylus 11 13 , and Cyrtodactylus 14 16 , is still controversial.…”
Section: Introductionmentioning
confidence: 99%